THE CLINICAL-IMMUNOLOGICAL CHARAC-TERISTIC OF CHRONIC INFLAMMATION IN PERIODONTIUM OF TEMPORARY TEETH - Шешукова, О.В. (World of Medicine and Biology, 2010)
In this article, the correlations of clinical symptoms with the presence of infectious agent in root canal of inflamed tooth are present, and also the morphological and immunological features of periapical granulation tissue. The character of microbic invasion under periodontium of temporary teeth directly influences on the stage of periapical granulation tissue which is being formed in response to the action on definite type of microorganisms and reproduces the infiltration of periapical granulative tissue by general subpopulation of lymphocyte and dendritic cells.